2021
DOI: 10.1002/cbic.202000745
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Sortases in Peptide and Protein Chemistry

Abstract: The transpeptidase sortase A of Staphylococcus aureus (Sa-SrtA) is a valuable tool in protein chemistry. The native enzyme anchors surface proteins containing a highly conserved LPxTG sorting motif to a terminal glycine residue of the peptidoglycan layer in Gram-positive bacteria. This reaction is exploited for sortase-mediated ligation (SML), allowing the site-specific linkage of synthetic peptides and recombinant proteins by a native peptide bond. However, the moderate catalytic efficiency and specificity of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 70 publications
1
28
0
Order By: Relevance
“…Sortase A from Staphylococcus aureus (saSrtA) was the first of these enzymes discovered and continues to see widespread use for in vitro SML experiments (1,7). Notable improvements in SML technology has occurred in recent years, including strategies for limiting the reversibility of the ligation reaction, and the development of saSrtA variants with dramatically improved catalytic J o u r n a l P r e -p r o o f efficiency (3,8,9). However, as a consequence of the narrow substrate selectivity of saSrtA (10), the majority of SML examples rely on the combination of one ligation partner displaying an LPXTG motif near its C-terminus with another possessing one or more N-terminal glycines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sortase A from Staphylococcus aureus (saSrtA) was the first of these enzymes discovered and continues to see widespread use for in vitro SML experiments (1,7). Notable improvements in SML technology has occurred in recent years, including strategies for limiting the reversibility of the ligation reaction, and the development of saSrtA variants with dramatically improved catalytic J o u r n a l P r e -p r o o f efficiency (3,8,9). However, as a consequence of the narrow substrate selectivity of saSrtA (10), the majority of SML examples rely on the combination of one ligation partner displaying an LPXTG motif near its C-terminus with another possessing one or more N-terminal glycines.…”
Section: Introductionmentioning
confidence: 99%
“…However, as a consequence of the narrow substrate selectivity of saSrtA ( 10 ), the majority of SML examples rely on the combination of one ligation partner displaying an LPXTG motif near its C-terminus with another possessing one or more N-terminal glycines. This restricted substrate scope can be advantageous, for example, in the use of SML for labeling specific polypeptides in complex mixtures, but it also represents a limitation for certain applications ( 9 , 11 , 12 ). Highlighting this point, an increasing number of studies have demonstrated that the use of naturally occurring sortases or engineered sortases with altered substrate selectivity offers distinct advantages such as reducing the necessity for point mutations in protein semisynthesis applications ( 12 ), enabling the labeling of endogenous proteins that do not naturally contain the LPXTG motif ( 11 , 13 ), and allowing labeling of multiple sites within the same protein target ( 11 , 14 ).…”
mentioning
confidence: 99%
“…A limit of the SrtA reaction over the hydrolysis of the product is also the low turnover rate of the reaction that necessitates a long incubation time and high enzyme concentration. Further engineering of the enzyme has improved the reaction kinetics of StrA, and it has provided an enzyme that does not depend on the presence of calcium ions and that displays a higher stability to temperature and in the presence of organic solvents (for a recent review on StrA engineering see Freund and Schwarzer [99]). An interesting possibility of StrA derivatization is the co-expression in E. coli of StrA and of the target protein fused at the C-terminus to the sortag.…”
Section: Sortasementioning
confidence: 99%
“…113,114 Overall, Sortase A-catalyzed reactions can provide milligram quantities of ligated product and allow the introduction of PTMs, which makes them an attractive tool for chemoenzymatic segmental labelling of proteins. 115,116…”
Section: Rsc Chemical Biology Accepted Manuscriptmentioning
confidence: 99%